(untitled) (Journal of the College of Basic Education, 2026)
This research is divided into an introduction and two sections. In the introduction, I discuss: the definition of ‘individual opinions,’ ‘consensus,’ ‘Imam Ibn al-Mundhir al-Nisaburi,’ and ‘Ibn al-Mundhir’s Book of Consensus.’ The first section discusses issues concerning ijma and infradat mentioned in Kitab al-Ijma by Ibn al-Mundhir al-Nisaburi (may Allah have mercy on him). The second section discusses two issues in which some imams and jurists deviated from ijma, comparing the opinions of the majority with those of the minority. The objectives of the research were: 1- To clarify the validity of calling it consensus if there is a dissenting opinion, and to clarify whether this constitutes a breach of consensus. 2- To clarify the reasons for the dissent of some jurists from the consensus. 3- To clarify the validity of weighing the opinions of the consensus and the dissenting opinions. 4. To clarify the prevailing opinion if it is permissible to give preference to the opinion of the majority over that of the minority in both issues addressed in this research. The most important results of this research were1- It appears that when Ibn al-Mundhir wrote his book on consensus, he sought to be accurate in his transmission of these consensuses, as evidenced by the two jurisprudential issues discussed by the researcher and the evidence he cited. Neither of the two models was devoid of at least one piece of evidence that could be used as proof, which the majority relied on in their consensus, or which could be used as proof for them, or which supported their proof and gave weight to their consensus over the opinion of the individual. 2. Consensus is not reached if the individual’s opinion is contrary to that of the majority of the consensus, according to the agreement of the four schools of thought of the consensus and most of the scholars who agreed with them. This opinion is preferred by the researcher over the opinion of the minority who disagreed with it. 3. Consensus is reached with the dissent of the individual if the assembly denies the individual’s dissent. If his dissent contradicts a text from the Qur’an or Sunnah. 4. Imam al-Sam’ani said that the truth may lie with the individual and not with the assembly, and he cited evidence for this, which the researcher accepted. Based on this, the researcher considered it permissible to give preference to the opinion of the majority over that of the minority, unless the majority rejected the minority’s opinion, as reported by Al-Jassas from a group of scholars. and unless the individual contradicts a text from the Qur’an or Sunnah, as stated by Imam al-Sam’ani. 5. Individualism is not considered a violation of consensus if it comes from someone who is sound in belief, correct in religion, and just. Rather, individualism is considered a violation if it comes from someone who is accustomed to violating consensus out of stubbornness and bias. This is the meaning of the words of Imam al-Juwaini Abd al-Malik, may Allah have mercy on him, on this issue. 6. It is not correct to call it consensus when there is a dissenting individual whose dissent has not been rejected by the consensus-makers and who has not contradicted the Qur’an or Sunnah. The correct term for this is ‘agreement.’ 7. Among the most important reasons for the isolation of the dissidents, as apparent in the two issues, are: A. Innovation, whereby the dissident innovates an act, as Imam Malik innovated prostration on the Black Stone, contrary to the consensus of those who say that it is recommended. B. Adherence to generality. Makhul adhered to the generality of the evidence on prostration for forgetfulness in all cases, contrary to the consensus of scholars who say that the imam is responsible for the prayer of the follower and that the follower is not responsible for forgetfulness if he follows the imam.